Genomic determination of the glucocorticoid response reveals unexpected mechanisms of gene regulation - Reddy, Timothy E.; Pauli, Florencia; Sprouse, Rebekka O.; Neff, Norma F.; Newberry, Kimberly M.; Garabedian, Michael J.; Myers, Richard M. (Genome Research, 2009)
The glucocorticoid steroid hormone cortisol is released by the adrenal glands in response to stress and serves as a messenger in circadian rhythms. Transcriptional responses to this hormonal signal are mediated by the glucocorticoid receptor (GR). We determined GR binding throughout the human genome by using chromatin immunoprecipitation followed by next-generation DNA sequencing, and measured related changes in gene expression with mRNA sequencing in response to the glucocorticoid dexamethasone (DEX). We identified 4392 genomic positions occupied by the GR and 234 genes with significant changes in expression in response to DEX. This genomic census revealed striking differences between gene activation and repression by the GR. While genes activated with DEX treatment have GR bound within a median distance of 11 kb from the transcriptional start site (TSS), the nearest GR binding for genes repressed with DEX treatment is a median of 146 kb from the TSS, suggesting that DEX-mediated repression occurs independently of promoter-proximal GR binding. In addition to the dramatic differences in proximity of GR binding, we found differences in the kinetics of gene expression response for induced and repressed genes, with repression occurring substantially after induction. We also found that the GR can respond to different levels of corticosteroids in a gene-specific manner. For example, low doses of DEX selectively induced PER1, a transcription factor involved in regulating circadian rhythms. Overall, the genome-wide determination and analysis of GR:DNA binding and transcriptional response to hormone reveals new insights into the complexities of gene regulatory activities managed by GR.
10.1101/gr.097022.109